Targeting ferroptosis: a promising avenue for ovarian cancer treatment - Wu, Xiaolan; Liu, Qizhi; Jiang, Zhili; Wang, Guiyun; Liao, Lingyu; Ye, Xiaojuan; Xing, Min; Sun, Han; Liu, Qiying; Liu, Huiping (Frontiers in Immunology, 2025)
Ovarian cancer(OC) is the second most common gynecological malignancy worldwide. While traditional treatments such as cytoreductive surgery, chemotherapy, and targeted drugs have made progress, patients with advanced disease still face high recurrence rates and resistance to treatment. As a result, there is an urgent need to develop new therapeutic strategies. Ferroptosis, a novel form of programmed cell death characterized by iron-dependent lipid peroxidation, has recently gained attention for its potential in cancer therapy. Studies indicate that OC cells are highly sensitive to ferroptosis, and targeting this pathway can effectively overcome chemotherapy resistance and improve treatment outcomes. This review systematically examines the molecular mechanisms of ferroptosis and its role in OC, with a focus on its involvement in tumor initiation, progression, TME and resistance. Furthermore, we highlight the research advancements on various ferroptosis inducers, including natural products, small molecule compounds, and nanotechnology, and explore their potential in overcoming resistance and enhancing patient prognosis. We also discuss the challenges facing ferroptosis-based treatments for OC, such as species differences, drug resistance, personalized treatment needs, and clinical translation issues. Ultimately, targeted modulation of ferroptosis offers new hope for OC therapy. Future research should focus on further elucidating its molecular mechanisms and exploring effective inducers and combination therapies to enhance its clinical applicability in precision and personalized medicine.